Implementation of Blockchain Technology for Securing Data Point Transactions in an IoT-Based Waste Sorting System - Naufal Raihan Elriza; Kasliono Kasliono; Hirzen Hasfani (Media of Computer Science, 2025)
An Internet of Things (IoT) based waste sorting device awards points to users who dispose of waste through it, as long as the user is registered in the system. However, despite these benefits, this system is vulnerable to various forms of cybercrime. One such challenge is the rise of data manipulation and cyberattacks such as sql injection and threats from internal parties (Insider Threats). This research aims to secure point data transactions in an Internet of Things (IoT) based waste sorting system integrated with blockchain technology to improve security in recording user point data. Tests were conducted to ensure that point data sent from IoT devices were successfully recorded on the blockchain network permanently and verified through transaction hashes in etherscan and to prevent sql Injection and Insider Threat attacks in attempts to illegally alter data. The results of the data transmission test to the blockchain network, which was carried out 30 times, showed that each transaction was successfully recorded and provided a transaction hash. In addition, the attack test, which was carried out 30 times, each attack resulted in a notification with the text “[PERINGATAN] Terjadi Percobaan Pengubahan Poin " in red. Using the blockchain network, both attacks failed to alter user points